The effects of advertisement disclosure on heavy and light Instagram users - Zofia Saternus; Patrick Weber; Oliver Hinz (Electronic Markets, 2022)
The present study investigates the moderating effect of usage intensity of the social networking site (SNS) Instagram (IG) on the influence of advertisement disclosure types on advertising performance. A national sample (N0.167em=0.167em566) participated in a randomized online experiment including a real influencer and followers in order to investigate how different advertisement disclosure types affect advertising performance and how usage intensity moderates this effect. We find that disclosing an influencer's postings with "#ad" increases the trustworthiness of the influencer and the general credibility of the posting for heavy users, but not for light users. Followership of a user has been found to strongly improve all researched variables (attitude toward product placement, trustworthiness of the spokesperson and general credibility of the posting). This study adds to literature the first distinction on heavy and light usage intensity, and on followership of an IG user when regarding the effects of advertisement disclosure types on advertising performance. To conclude, we present a number of recommendations regarding how advertisers, influencers, and SNS providers should develop strategies for monitoring, understanding, and responding to different social media users, e.g., to closely monitor an influencer's audience to identify heavy users and optimally target them.
Keywords: C21; C83; C90; D18; D82; K21; M37; Z18; 620; Advertisement disclosure; Heavy and light users; Usage intensity; Social networking site; Influencer marketing; Advertising performance